Single source-based energy and efficiency calibration method for the assessment of an alpha imaging detector. (13th December 2021) - Kim, G.; Lim, I.; Kim, B.; Song, K.; Kim, J.-G.
Abstract: An alpha imaging detector acquires a two-dimensional distribution of a sample that emits alpha particles. For the quantitative analysis of the image of an alpha-emitting sample, the individual energies of the alpha particles must be identified, which can be achieved using the spectrometric method after detector calibration. In this study, an energy and efficiency calibration method was investigated to assess an alpha imaging detector. The calibration was performed using a single standard source of Am-241 based on the energy loss characteristic of an alpha particle. The feasibility of the calibration method was evaluated using another source, Ac-225. The calibrated alpha imaging detector was evaluated in terms of energy resolution and detection efficiency, and the alpha imaging detector was found to be efficiently calibrated using a single standard source. The calibrated alpha imaging detector appears promising for the quantitative analysis of samples that emit alpha particles.